The quality movement's three operational paradigms: a text mining venture. Issue 6 (28th February 2020) - Carnerud, Daniel
Abstract : Purpose: This study aims to analyze four text-mining studies of quality management (QM) to illustrate and problematize how the research on quality has informed the quality paradigm since the 1980s. By understanding history, one can better manage current developments. Design/methodology/approach: The findings are based on a meta-analysis of four text-mining studies that explore and describe 11, 579 research entries on quality between 1980 and 2017. Findings: The findings show that the research on quality during the past 30 years form a research paradigm consisting of three operational paradigms: an operative paradigm of backend quality orbiting around QM, total QM (TQM) and service quality; an operative paradigm of middle-way quality, circling around the International Organization for Standardization (ISO), business excellence frameworks (BEFs) and quality awards; and an operative paradigm of frontend quality, revolving around reliability, costs and processes. The operative paradigms are interconnected and complementary; they also show a divide between a general management view of quality and a hands-on engineering view of quality. The findings indicate that the research on quality is a long-lived standalone paradigm, supporting the notion of quality being a genuine academic entity, not a fashion or fad. Research limitations/implications: The empirical basis of the study is four text-mining studies. Consequently, the results and findings are based on a limited number of findings. Originality: Text-mining studies targeting research on quality are scarce, and there seem to be no prior models that depict the quality paradigm based on such studies. The perspectives presented here will advance the existing paradigmatic discourse. The new viewpoints aim to facilitate and deepen the discussion on current and future directions of the paradigm.